Розроблення і оцінка якості плодових напоїв із підвищеним вмістом біологічно активних речовин - Василишина, Олена Володимирівна; Токар, Анастасія Юхимівна; Заморська, Ірина Леонідівна; Гайдай, Ірина Володимирівна; Калайда, Катерина Василівна; Худік, Людмила Миколаївна; Vasylyshyna, Olena; Tokar, Anastasiia; Zamorska, Iryna; Haidai, Iryna; Kalayda, Kateryna; Khudik, Liudmyla (Запоріжжя : Видавничій дім "Гельветика", 2025)
UA: Статтю присвячено розробці соків функціонального спрямування з додаванням дигідрокверцетину як біологічної активної добавки. Для проведення досліджень відбирали плоди яблук сорту Амулет, вишні сорту Альфа та малини сорту Новокитаївська. Встановлено, що для збагачення вітаміном С напоїв доцільно додавати дигідрокверцетин у кількості 20 мг/л. Напої з додаванням дигідрокверцетину відповідають вимогам стандарту, за кількістю сухих розчинних речовин їх вміст становив – 11 %, титрованих кислот – 0,8−0,9 %, загальних цукрів − 8,3 і 8,6 %, дубильних речовин – 0,6−0,7 %, аскорбінової кислоти − 30,8−31,6 мг/100 г. Отpимані напої мають значний вміст біологічно активних речовин та антиоксидантної активності − 3,8−4,2 ммоль/дм3. За органолептичними показниками напої мали відмінну дегустаційну оцінку, тож їх можна віднести до продуктів функціонального харчування. /// EN: The article is devoted to the development of functional juices with the addition of dihydroquercetin as a biologically active supplement. Fruit juices are beverages that have biological value and dietary properties, made from fresh, ripe fruits. The biological value of juices is due to the presence of vitamins and minerals in them. For example, cherry, apricot, grape, raspberry, and blackberry juices have a significant content of potassium and iron. Directly pressed juices are preserved using a physical method (ionizing radiation) without the use of preservatives, so they have a limited shelf life of no more than one month. The main cause of juice spoilage is radical and peroxide oxidation due to active forms of oxygen released as a result of the vital activity of microorganisms and the formation of significant concentrations of organic acids. The solution to the problem lies in the addition of natural antioxidants, in particular dihydroquercetin. Dihydroquercetin is a polyphenol, a flavonoid from the quercetin group, a natural antioxidant found in larch and coniferous trees and in milk thistle seeds. Amulet apples, Alpha cherries, and Novokitaevskaya raspberries were selected for the study. It was found that to enrich beverages with vitamin C, it is advisable to add 20mg/l of dihydroquercetin. Beverages with added dihydroquercetin meet the standard requirements for dry soluble substances, which was 11 %, titrated acids – 0.8–0.9 %, total sugars – 8.3 and 8.6 %, tannins – 0.6–0.7 %, and ascorbic acid – 30.8–31.6 mg/100 g. The resulting beverages have a significant content of biologically active substances and antioxidant activity – 3.8–4.2 mmol/dm3. According to organoleptic indicators, the beverages had an excellent taste rating and can be classified as functional foods.
Development and quality assessment of fruit drinks with increased content of biologically active substances
Keywords: напої; біологічно активні речовини; дигідрокверцетин; вітамін С; дубильні та барвні речовини; beverages; biologically active substances; dihydroquercetin; vitamin C; tannins; pigments